Accuracy of prediction scores and novel biomarkers for predicting nonalcoholic fatty liver disease in obese children12. (16th April 2013) - Koot, Bart G.P.; van der Baan‐Slootweg, Olga H.; Bohte, Anneloes E.; Nederveen, Aart J.; van Werven, Jochem R.; Tamminga‐Smeulders, Christine L.J.; Merkus, Maruschka P.; Schaap, Frank G.; Jansen, Peter L.M.; Stoker, Jaap; Benninga, Marc A.
Abstract Background: Accurate prediction scores for liver steatosis are demanded to enable clinicians to noninvasively screen for nonalcoholic fatty liver disease (NAFLD). Several prediction scores have been developed, however external validation is lacking. Objective: The aim was to determine the diagnostic accuracy of four existing prediction scores in severely obese children, to develop a new prediction score using novel biomarkers and to compare these results to the performance of ultrasonography. Design and Results: Liver steatosis was measured using proton magnetic resonance spectroscopy in 119 severely obese children (mean age 14.3 ± 2.1 years, BMI z‐score 3.35 ± 0.35). Prevalence of steatosis was 47%. The four existing predictions scores ("NAFLD liver fat score, " "fatty liver index, " "hepatic steatosis index, " and the pediatric prediction score) had only moderate diagnostic accuracy in this cohort (positive predictive value (PPV): 70, 61, 61, 69% and negative predictive value (NPV) 77, 69, 68, 75%, respectively). A new prediction score was built using anthropometry, routine biochemistry and novel biomarkers (leptin, adiponectin, TNF‐alpha, IL‐6, CK‐18, FGF‐21, and adiponutrin polymorphisms). The final model included ALT, HOMA, sex, and leptin. This equation (PPV 79% and NPV 80%) did not perform substantially better than the four other equations and did not outperform ultrasonography for excluding NAFLD (NPV 82%). Conclusion: The conclusion is in severely obese children and adolescents existing prediction scores and the tested novel biomarkers have insufficient diagnostic accuracy for diagnosing or excluding NAFLD.